Empowerment Evaluation : Knowledge and Tools for Self-Assessment, Evaluation Capacity Building, and Accountability /: Knowledge and Tools for Self-Assessment, Evaluation Capacity Building, and Accountability. ([2015]) - Unknown
No abstract available